The Cyclin-Dependent Kinase Inhibitor KRP6 Induces Mitosis and Impairs Cytokinesis in Giant Cells Induced by Plant-Parasitic Nematodes in Arabidopsis . Issue 6 (24th June 2014) - Vieira, Paulo; De Clercq, Annelies; Stals, Hilde; Van Leene, Jelle; Van De Slijke, Eveline; Van Isterdael, Gert; Eeckhout, Dominique; Persiau, Geert; Van Damme, Daniël; Verkest, Aurine; Antonino de Souza, José Dijair; Júnior; et al.
Abstract : This work points to an unexpected role for KRP6 during mitosis, suggesting that not all KRPs regulate the cell cycle in the same manner. The findings support the idea that plant-parasitic nematodes have evolved the ability to exploit plant cell cycle genes to the benefit of gall establishment. Abstract: In Arabidopsis thaliana, seven cyclin-dependent kinase (CDK ) inhibitors have been identified, designated interactors of CDKs or Kip-related proteins (KRPs ). Here, the function of KRP6 was investigated during cell cycle progression in roots infected by plant-parasitic root-knot nematodes. Contrary to expectations, analysis of Meloidogyne incognita –induced galls of KRP6 -overexpressing lines revealed a role for this particular KRP as an activator of the mitotic cell cycle. In accordance, KRP6 -overexpressing suspension cultures displayed accelerated entry into mitosis, but delayed mitotic progression. Likewise, phenotypic analysis of cultured cells and nematode-induced giant cells revealed a failure in mitotic exit, with the appearance of multinucleated cells as a consequence. Strong KRP6 expression upon nematode infection and the phenotypic resemblance between KRP6 overexpression cell cultures and root-knot morphology point toward the involvement of KRP6 in the multinucleate and acytokinetic state of giant cells. Along these lines, the parasite might have evolved to manipulate plant KRP6 transcription to the benefit of gall establishment.